MENTAL HEALTH AND MEDIATION IN ATTORNEYS’ PROFESSIONAL PRACTICE - Proskuriakov, Serhii; Ihnatovych, Olena (My University, 2025)
Purpose. The article presents the results of a study conducted to theoretically substantiate and empirically examine the psychological characteristics of using mediation in attorneys’ professional practice as factors for preserving an individual’s mental health. Methods. To achieve this purpose, the following methods were used: analysis of scientific and popular scientific sources; psychological diagnostics using the R. Kettel’s 16-PF Multifactor Personality Inventory. Descriptive statistics used to process and interpret the results of psychological diagnostics. Results. The main study findings include substantiating principles of cultural and professional determination and the mediated self-activity development of mediation practitioners as initial provisions of personal and professional approach. The study drafts the attorney-mediator’s professional profile, highlighting the psychological characteristics of mediation as a component of attorney’s professional practice and identifying key professionally important personal qualities critical to preserving an individual’s mental health and attorneys’ effective mediating. Conclusions. The study findings serve as a basis for developing further support programme focused on restoring and preserving an individual’s mental health in the context of using mediation in attorney’s professional practice, as well as recommendations for enhancing mediation practice of attorneys to preserve legal professionals’ mental health.

Мета. У статті представлено результати дослідження, проведеного з метою теоретичного обґрунтування та емпіричного вивчення психологічних особливостей використання медіації в професійній діяльності адвокатів як чинників збереження психічного здоров’я особистості. Методи дослідження. Для досягнення поставленої мети були використані такі методи: аналіз наукових і науково-популярних джерел; психологічна діагностика за допомогою багатофакторного особистісного опитувальника Р. Кеттелла (16-PF). Для обробки та інтерпретації результатів психологічної діагностики застосовувалась описова статистика. Результати. Основні висновки дослідження включають обґрунтування принципів культурної та професійної детермінації, а також розвитку опосередкованої самодіяльності медіаторів як вихідних положень особистісного та професійного підходу. У дослідженні окреслено професійний профіль адвоката-медіатора, висвітлено психологічні особливості медіації як складової професійної діяльності адвоката та визначено ключові професійно важливі особистісні якості, критично важливі для збереження психічного здоров’я особистості та ефективного медіювання адвокатами. Висновки. Отримані результати слугують основою для розробки подальших програм підтримки, спрямованих на відновлення та збереження психічного здоров’я особистості в контексті використання медіації в професійній діяльності адвокатів, а також рекомендацій щодо вдосконалення медіативної практики адвокатів з метою збереження психічного здоров’я правників.
Keywords: interdisciplinarity; mediation in attorney’s practice; mental health of an attorney-mediator; personal and professional approach; mediation; psychological and ethical principles of mediation; professional qualities of an attorney-mediator